Resposta da cultura do milho a diferentes fontes de enxofre e formas de aplicação de micronutrientes - Fiorini, Ivan Vilela Andrade (2011)
With the purpose of evaluating the rate of absorption of nutrients dry matter and agronomic efficiency of fertilizers in corn crop associated to two sources of sulfur and two forms of micronutrients, experiments were conducted in both greenhouse and field. In greenhouse was utilized hybrid DKB390 evaluated under a completely randomized design in factorial scheme 2 (soils) x 3 (fertilizers) x 6 (phenological stages) with three replicates. The soil of cultivating of corn monoculture area and the ravine soil never cultivated were utilized. Three types of formulated fertilizers (NPK), associated with sulfur (ammonium sulfate or elemental sulfur) and the control without S, were used. The accumulation of nutrients in the leaf, shoot and root dry matters was evaluated. The data were collected at six stages: E1 (6 leaves), E2 (10 leaves), E3 (14 leaves), E4 (tasseling), E5 (flowering) and E6 (physiological maturity). The fertilizers provided differences in the shoot dry matter and in the accumulations of nitrogen, sulfur and magnesium. The accumulation of sulfur in the elementary form in corn is similar to that obtained with the sulfur of ammonium sulfate. Elemental sulfur provided results superior to the fertilizer without sulfur and similar to the fertilizer with ammonium sulfate in Lavras-MG and one in um Ijaci-MG in no-tillage planting established in November/2009. The experiment in conventional system was established in December/2009 in Lavras-MG. The design was in randomized blocks with five replicates in factorial scheme 3 x 2, that is, three fertilizers, one without sulfur and the other two with different sources of sulfur (elemental sulfur or ammonium sulfate), associated to two forms of micronutrients (granular or coated granule). No differences were found for sources of sulfur and forms of supplying micronutrients. The different sources of sulfur affect the characteristics in a similar way and do not depend on the form of the micronutrients. The replacement of sulfur coming from ammonium sulfate by elemental sulfur in NPK fertilizers or even the absence of this in fertilizers will not endanger the agronomic efficiency of fertilizers.